Pengaruh Konten @nex.carlos terhadap Pemenuhan Kebutuhan Informasi Wisata Kuliner di TikTok - Nisa, Nauryn; Siti Meisyaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Social media development provides not only entertainment but also information tailored to TikTok users’ needs, including the culinary tourism content of @nex.carlos. This study aims to examine the impact of food vlogger Nex Carlos’ TikTok content on fulfilling culinary information needs among users. The research employs New Media theory and information needs theory to explain interactive, two-way digital communication and users’ efforts to seek information through the internet. A quantitative explanatory method was used, with data collected through a survey questionnaire distributed to Communication Science students of IBI Kwik Kian Gie. Fifty-seven respondents were selected using purposive sampling. Data were analyzed using normality, linearity, correlation, simple linear regression, coefficient of determination, and hypothesis tests. The results show a very strong and positive correlation, indicating that Nex Carlos’ food vlogger content significantly influences the fulfillment of culinary information needs of TikTok users.